Snapshot: Finding Japanese Scientific & Technical Information in 2014 - Ann Coppin (Issues in Science and Technology Librarianship)
The article discusses a draft document from the Japan Information Centre of Science and Technology (JICST) entitled "Finding Japanese Sources in Dialog Engineering Files." It says that the guide focuses on Japanese databases about scientific and technical publications. It mentions that the guide includes Web sites that permit searching of publications with English terms.